Berberine hydrochloride inhibits the proliferation and metastasis of p53 mutant gallbladder Cancer cells by regulating the IL6/STAT3 pathway - Huan Zhang; Guoning Li; Lanxin Ni; Rui Wang; Lijun Peng; Lanlan Zang; Chunlei Lu; Zhi Wang; Jinghua Liu (Scientific Reports)
Abstract Gallbladder cancer (GBC) is one of the most common biliary malignancies. Berberine hydrochloride, an compound extracted from the traditional Chinese medicinal plant Coptis chinensis, has potential therapeutic effects on various tumor cells. Therefore, we aimed to characterize the anticancer efficacy of berberine hydrochloride in the context of GBC. Methods: We evaluated the effects of berberine hydrochloride on cell viability, cell cycle progression, apoptosis, metastasis and invasion in the p53 mutant GBC-SD and p53 wild-type NOZ cell lines. Next, we investigated the mechanism underlying the effects of berberine hydrochloride on GBC cells via analysis of a human apoptosis proteome profiler array and a human inflammation array, and we confirmed the mechanism. Furthermore, we analyzed the ability of berberine hydrochloride to inhibit tumor formation in a liver xenograft model. Results: Berberine hydrochloride influenced the cell proliferation, apoptosis, cytoskeletal arrangement, metastasis and invasion of GBC cells, especially p53-mutant GBC-SD cells, by reducing interleukin-6 and p-STAT3 expression, triggering an inflammatory response resulting in apoptosis induction via caspase-3, caspase-8, and XIAP. Conclusion: In GBC cells, berberine hydrochloride inhibited the IL-6/STAT3 pathway and then induced apoptosis, ultimately exerting various biological effects. This study provides new insights for therapeutic targets in GBC.